Expert system for the thermal design of mechanical devices - Mohiuddin, A. K. M. (2003)
Expert system is an intelligent computer program that contains a large body of knowledge concerning one special field, this having been provided by one or more human experts in that field, and is able to achieve the same performance in problem-solving as the experts. Expert systems are computer programs that aim to model the rational behavior and performance of human experts. The author has developed an Expert System for the thermal design of wet cooling towers using artificial intelligence as a tool. A cooling tower is a device that is used to cool water by a simultaneous process of heat and mass transfer. Based on the experience the author likes to chalk out a general procedure for the development of expert system for the thermal design of different mechanical devices.